Inside Cover: Helical Colloidal Sphere Structures through Thermo‐Reversible Co‐Assembly with Molecular Microtubes (Angew. Chem. Int. Ed. 12/2013). Issue 12 (1st March 2013) - Jiang, Lingxiang; de Folter, Julius W. J.; Huang, Jianbin; Philipse, Albert P.; Kegel, Willem K.; Petukhov, Andrei V.
<x xml:space="preserve">Abstract</x> Hierarchical self‐assembly is often exploited by nature to build complex functional entities. A similar approach yielded a library of dynamic colloid‐in‐tube structures, such as colloidal zigzags, double‐ and triple‐helices, by utilizing the thermo‐reversible co‐assembly of colloidal spheres and molecular microtubes, as reported by J. Huang, A. V. Petukhov, et al. in their Communication on page 3364 ff. The assembly and disassembly of these structures near human body temperature was explored in situ and in real time.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>